Remarks on some interesting African Pamphagidae and Acrididae (Insecta: Orthoptera: Acridoidea) - Massa, Bruno (Zootaxa, 2020)
The author reports about the results of a study of Porthetinae (Pamphagidae) and other Acridoidea preserved in some European museums. The taxonomy of African Porthetinae is still poorly known; some genera were established on variable characters (e.g.: the number of the flagellum segments, the shape of the hind femora or the prosternal tubercle) and collections generally hold only few specimens of this group. These insects are characterized by a remarkable sexual dimorphism, the males generally are winged while females are apterous. Because many species were described only from one sex (sometimes the female sex), there are objective difficulties to identify them correctly. The following synonymies are proposed here: Pagopedilum Karsch, 1896 = Stolliana Bolívar, 1916; Pagopedilum brevis (Walker, 1870) = Pagopedilum martini Bolívar, 1915; Cultrinotus poultoni Bolívar, 1915 = Cultrinotus luanensis Uvarov, 1953. The male of Pagopedilum bradyanum (Saussure, 1887) and adults male and female of Pagopedilum brevis (Walker, 1870) (known only from the nymph) are described. The distinction of the genera Lobosceliana Dirsh, 1958 and Xiphoceriana Dirsh, 1958 is revealed to be very difficult and they are probably synonyms, but more material should be studied. The stridulatory system found in different genera of Porthetinae is briefly described. Further, the South African Batrachotetrix cantans Saussure, 1888 (Pamphagidae: Akicerinae) is recorded for the first time in Namibia, Barombia tuberculosa sublaevis Bolívar, 1905 (Acrididae: Catantopinae) is synonymized with B. t. tuberculosa Karsch, 1891, a probable new brachypterous species of Rhachitopis (Acrididae: Euryphyminae) is reported from Angola, the Namibian Pycnodictya herero Karny, 1910 (Acrididae: Oedipodinae) is recorded for the first time from Angola, and the Tanzanian Tmetonota dispar Miller, 1929 (Acrididae: Oedipodinae) is recorded for the first time from Kenya.